2006
DOI: 10.1037/0021-843x.115.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain electrical activity in posttraumatic stress disorder after motor vehicle accident.

Abstract: This study examined whether patients with posttraumatic stress disorder (PTSD) related to motor vehicle accidents (MVAs) would show an abnormal pattern of electroencephalographic (EEG) alpha asymmetries, which has been proposed for particular types of anxiety. Patients with PTSD (n = 22) or subsyndromal PTSD (n = 21), traumatized controls without PTSD (non-PTSD with MVA; n = 21), and healthy controls without MVA (n = 23) underwent measurement of EEG activity during baseline and exposure to a neutral, a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 62 publications
10
85
2
Order By: Relevance
“…Using a restingstate paradigm to observe the alpha asymmetry, Kemp et al (2010) found greater right-frontal activity in association with more-severe PTSS. However, Rabe et al (2006a) did not find significant associations in their resting-state paradigm, consistent with other works (Rabe et al, 2006b;Shankman et al, 2008), but they did find greater right-frontal activity to be associated with greater PTSS severity when the subjects viewed trauma-related pictures. Given the inverse relationship between alpha power and cortical activity (Oakes et al, 2004), a decrease in alpha power is assumed to reflect an increase in cortical activity.…”
Section: Eeg Spectral Analysis Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…Using a restingstate paradigm to observe the alpha asymmetry, Kemp et al (2010) found greater right-frontal activity in association with more-severe PTSS. However, Rabe et al (2006a) did not find significant associations in their resting-state paradigm, consistent with other works (Rabe et al, 2006b;Shankman et al, 2008), but they did find greater right-frontal activity to be associated with greater PTSS severity when the subjects viewed trauma-related pictures. Given the inverse relationship between alpha power and cortical activity (Oakes et al, 2004), a decrease in alpha power is assumed to reflect an increase in cortical activity.…”
Section: Eeg Spectral Analysis Studiessupporting
confidence: 88%
“…In other studies(Rabe et al, 2006b;Shankman et al, 2008), neither alpha, beta nor theta asymmetries in the frontal, central or posterior regions was correlated with PTSS.Another work investigated the alpha asymmetry in an emotion paradigm in patients with PTSD who were victims of motor vehicle accidents (MVA), subsyndromal PTSD (MVA), traumatized controls (without PTSD with MVA), and healthy controls (without MVA). EEG was recorded during baseline and exposure to neutral, positive, negative, and accident-related pictures(Rabe et al, 2006a).Alpha asymmetry scores (right minus left hemisphere) for the frontal and parietal regions were recorded. Although the authors did not find any correlation between the EEG baseline and PTSS, when they computed the alpha asymmetry scores for the anterior and posterior regions on the basis of the EEG alpha power change scores (neutral minus emotion condition), significant correlations were found.…”
mentioning
confidence: 99%
“…The MMN might therefore be a valuable tool for the research of basic physiological changes in PTSD. Newest results suggest asymmetric processing in PTSD (Lepisto et al, 2004;Rabe et al, 2006). Further studies might show whether this highly differential processing of auditory features corresponds to an asymmetry in hemispheric processing.…”
Section: Discussionmentioning
confidence: 81%
“…In a recent study, we examined brain electrical activity in motor vehicle accident (MVA) survivors with PTSD, subsyndromal PTSD, and without PTSD as well as healthy controls without severe MVA during baseline and during confrontation to neutral, positive, negative, and trauma-related pictures (12). We found that participants with PTSD and subsyndromal PTSD showed a pattern of enhanced right anterior and posterior activation in response to the trauma-related accident picture.…”
Section: Introductionmentioning
confidence: 94%